Personality and job creativity in relation to engagement in nursing - Molero Jurado, María del Mar; Pérez-Fuentes, María del Carmen; Soriano, José Gabriel; Tortosa, Begoña María; Fátima Oropesa, Nieves; Simón Márquez, María del Mar; Gázquez Linares, José Jesús (Anales de Psicología / Annals of Psychology, 2020)
Personality is made up of a series of individual attributes characterized by how one thinks, feels or acts, which are influenced by both endogenous and exogenous factors. Thus, personality presents an influence on various constructs, such as the perception of job creativity and engagement. The objective of this study was to analyze the effect of personality and perception of job creativity on engagement in nursing. A sample of 1268 nursing professionals, 22 to 63 years old, was evaluated. Data were collected with several different instruments, such as the Big Five Inventory (BFI-10), the Creative Environment Perceptions (CEP) scale and the Utrecht Work Engagement Scale (UWES). The data found suggest that Neuroticism is negatively related to the perception of creativity and with engagement, just as the Creativity blocking factor was not related to engagement. The results indicate that more creative and engaged nursing personnel present more stability, lower anxiety and tension and fewer problems with the organization. They also show more enthusiasm and cheer, and with it, more competence and creativity in the institutional organization they are part of.